Organizational culture and teacher performance management at the Túpac Amaru educational institution, Lima. - Sulca Gutierrez , Alejandrina (2025)
One of the current trends is how to ensure that students in regular primary and secondary education achieve quality learning outcomes.  For this reason, research has been conducted demonstrating a significant relationship between organizational culture and teacher performance. Therefore, we decided to build upon previous research conducted in other institutions and carry out a study at the Túpac Amaru School in Villa María del Triunfo, Lima. This study employed a quantitative approach, a deductive-hypothetical method, an ordinal scale, and a cross-sectional design, with a sample of 71 teachers. Two data collection instruments were used, validated by three expert panels and assessed for reliability using Cronbach's alpha.  Descriptive statistics and Spearman's rho correlation coefficient were used for data analysis. The results showed a moderate, significant correlation between organizational culture and teacher performance (Spearman's rho = 0.702, p = 0.002 < 0.05).  This indicates that the stronger the organizational culture within the school, the better the teacher performance will be.